Comparative Effects of Er-Xian Decoction, Epimedium Herbs, and Icariin with Estrogen on Bone and Reproductive Tissue in Ovariectomized Rats. (7th November 2012) - Xue, Liming; Wang, Yin; Jiang, Yiping; Han, Ting; Nie, Yan; Zhao, Lu; Zhang, Qiaoyan; Qin, Luping
Abstract : Er-Xian Decoction (EXD), Epimedium herbs (herbs of Epimedium brevicornum Maxim, EBH), and icariin (ICA) have been proven to have estrogen-like and antiosteoporotic activity and are used for the treatment of osteoporosis, menopausal syndrome, and age-associated diseases. The present study found that EXD, EBH, and ICA treatments, emulating estrogen, significantly contributed to bone density and architecture in OVX rats and that EXD is similar to estrogen and exerts a concomitant effect on bone formation and bone resorption at the tissue level, while EBH and ICA produced bone-protective effects mainly by inhibiting bone resorption. Nevertheless, EXD, EBH, and ICA treatments manifested a fewer adverse effects on the uterus, mammary gland, and vagina compared to estrogen administrations. Among the EXD, EBH, and ICA, EXD was found to have superior efficacy and safety profile.